The acculturation experiences of (and with) immigrant athletes. - Schinke, Robert J.; McGannon, Kerry R. (International Journal of Sport & Exercise Psychology, 2014)
The acculturation processes of immigrant athletes have recently been considered in sport psychology [Kontos, A.P. (2009). Multicultural sport psychology in the United States. In R.J. Schinke & S.J. Hanrahan (Eds.),Cultural sport psychology(pp. 103–116). Champaign, IL: Human Kinetics; Schinke, R.J., Yukelson, D., Bartolacci, G., Battochio, R.C., & Johnstone, K. (2011). The challenges encountered by immigrated elite athletes.Sport Psychology in Action,2, 1–11. doi:10.1080/21520704.2011.556179]. The practical relevance of the findings is limited, leaving practitioners with an insufficient understanding of how to engage with immigrant athletes during acculturation processes and enhance psychological outcomes in sport contexts. In the present article, the authors explore limitations within sport acculturation literature by drawing upon writings from cultural psychology to suggest that acculturation is a shared and fluid process [Chirkov, V. (2009). Critical psychology of acculturation: What do we study and how do we study it, when we investigate acculturation.International Journal of Intercultural Relations,33, 94–105. doi:10.1016/j.ijintrel.2008.12.004]. Based on these writings, it is then proposed that acculturation be viewed, either with a specific focus on the immigrant athlete, or shared with others, including teammates, coaches and sport scientists. Three possible forms of acculturation are then proposed: (1) acculturation as the athlete's responsibility, (2) limited reciprocity, and (3) immersed reciprocity. Suggestions for effective acculturation practices and research are provided.